Utilization of the Real Angklung Application in Cultural Arts Education to Improve High School Student Angklung Playing Skills - Lia Febria Kurnianingsih; Tri Karyono; Ayo Sunaryo (JTP - Jurnal Teknologi Pendidikan, 2026)
The low level of student skills in playing the angklung in the Cultural Arts subject shows that the traditional music practice learning process is not yet fully optimal. This condition is reflected in the learning achievement that is still below the set criteria, as well as the low level of active student involvement in practice activities. This problem requires learning innovations that can facilitate independent practice, collaboration, and systematic mentoring. This study aims to analyze the effectiveness of using the Real Angklung application in improving high school student' angklung playing skills. The method used is Classroom Action Research (CAR) conducted in two cycles, including the planning, implementation, observation, and reflection stages. There were 34 student participating in this study. Data were obtained through observation and practical tests, then analyzed quantitatively and descriptively using the percentage of learning completeness. The results showed an increase in mastery from 55.88% in the pre-cycle to 67.65% in Cycle I and further increased to 88.24% in Cycle II. Thus, the use of the Real Angklung application proved to be effective in improving student' angklung playing skills gradually and continuously.